Growth of Monolayer Molybdenum Disulfide and Diselenide with Chemical Vapor Deposition - WANG, X.; CHOW, W. L.; GUSAKOVA, J.; TAY, B. K.; LIU, Z. (PHYSICS, CHEMISTRY AND APPLICATIONS OF NANOSTRUCTURES, 2015)
Monolayer molybdenum disulfide (MoS2) and diselenide (MoSe2), as semiconductors with a direct band gap, have attracted much attention recently due to their novel properties, and potential application in field effect transistors, photo-electronics, spintronics, valleytronics. Previously, monolayer MoS2 or MoSe2 were exfoliated with an adhesive tape. Here, both monolayer MoS2 and MoSe2 are synthesized with a very simple chemical vapor deposition method. The as-grown samples are characterized with Raman and photoluminescence, demonstrating the samples are monolayer.